Developing professional communicative intercultural competence (PCIC) in legal education: integrating language, culture, and technology - Salimjonova, Nodira (The Lingua Spectrum, 2025)
This article examines the development of Professional Communicative Intercultural Competence (PCIC) in legal education, highlighting its vital role in preparing law students for globalized professional environments. Effective legal communication increasingly requires not only linguistic accuracy but also intercultural awareness and adaptability. The study analyzes innovative pedagogical approaches – such as collaborative learning, experiential practice, interdisciplinary co-teaching, and AI-driven simulations – that foster intercultural and communicative skills in future legal professionals. Particular attention is given to the context of Uzbek legal education, where traditional teaching methods often limit opportunities for intercultural engagement. The article identifies key challenges, including curriculum rigidity and limited teacher training, as well as emerging opportunities linked to technological integration and experiential learning. It argues that embedding PCIC in legal education enhances both professional and ethical competence, enabling law graduates to communicate effectively across cultures and contribute to more inclusive and globally responsive legal practice.